LEARNING MOTIVATION OF CHARACTERS IN LASKAR PELANGI BY ANDREA HIRATA - Dariswanto, Suad Vandana; Kasiyun, Suharmono; Authar, Nailul (Universitas Islam Balitar, 2021)
This research is a qualitative descriptive study that aims to find out high motivation of student in learning in remote villages, Belitong. In the LaskarPelangi novel There are many implicit and explicit messages of high motivation and enthusiasm for learning ten students of SD Muhammadiyah, Belitong..Motivation has an important influence in learning. This is one of the factors that greatly determines student learning outcomes, in this case makes the behavior to work or learn with full of initiative, creative and directed. Students who have high motivation to learnwill always try to be better and want to be succeedin their environment.